PENGARUH KELEKATAN REMAJA DENGAN IBU, AYAH, DAN TEMAN SEBAYA TERHADAP KENAKALAN REMAJA DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KELAS II BANDUNG - Fitriani, Wihelmina; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Adolescents delinquency that leads to criminal conduct had to be reviewed to identify the factor that causes it. This study aimed to analyze the influence of mother-adolescent, father-adolescent, and peer group-adolescent attachments on adolescent delinquency in Lembaga Pembinaan Khusus Anak (LPKA) Kelas II Bandung. The population were 157 adolescents known as andikpas (Anak Didik Lapas) with age range from15-18 years old. Participants of the study were 63 andikpas who had been randomly selected from LPKA Kelas II Bandung. Data were collected using interview technique with the questionnaire as the tools. Inventory of Parent and Peer Attachment (IPPA), and the Adapted Self Report Delinquency Scale (ASRDS) were used in the study. The result showed that adolescent had insecure attachment with mother, father, and peer group. Regression analysis showed that father-adolescent attachment had negative effect on adolescent delinquency. This showed that insecure attachment with father increased adolescent’s delinquent behaviors. The result also showed that peer group-adolescent attachment had positive effect on adolescent delinquency. This showed that peer group increased the risk for adolescent to conduct delinquent behavior that leads to criminal conduct.